Electrical properties of cation-substituted Ag₇(Si₁₋ₓGeₓ)S₅I single crystals - Studenyak, I.P.; Pogodin, A.I.; Shender, I.A.; Filep, M.J.; Kokhan, O.P.; Kopčanský, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
High-quality single crystals of Ag₇(Si₁₋ₓGeₓ)S₅I (x = 0.2, 0.4, 0.6, 0.8) solid solutions are grown from the solution–melt by the vertical zone crystallization method. The measurements of electrical conductivity of Ag₇(Si₁₋ₓGeₓ)S₅I solid solutions were performed using the impedance spectroscopy method within the frequency range from 10 Hz up to 2·10⁶ Hz and temperature interval 293–383 K. Ionic and electronic components of electrical conductivity, as well as their ratios, were determined using the Nyquist plots. Якісні монокристали твердих розчинів Ag₇(Si₁₋ₓGeₓ)S₅I (x = 0.2, 0.4, 0.6, 0.8) вирощені із розчину-розплаву методом вертикальної зонної кристалізації. Вимірювання електропровідності твердих розчинів Ag₇(Si₁₋ₓGeₓ)S₅I проведено методом імпедансної спектроскопії в діапазоні частот від 10 Гц до 2·10⁶ Гц та в температурному інтервалі 293–383 К. Іонні та електронні компоненти електропровідності, а також їх співвідношення визначали за допомогою діаграм Найквіста.